Impact of Profitability and Liquidity on Firm Value in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange (2018-2022) - Melati, Septi; Utomo, Rifais; Fathir, Khairil; Hamzah, M. Imron (Pascasarjana Universitas Pasundan, 2023)
This study aims to determine the effect of profitability and liquidity on the value of food and beverage sub-sector companies listed on the IDX in 2018-2022. This research is a quantitative study. The population of this study consisted of 15 companies using the purposive sampling method, the sample used was only 10 companies with details of 10 x 5 = 50 samples. Multiple linear regression analysis was used to analyze the effect of profitability and liquidity on company value using SPSS 25 software. The test results showed that profitability had a positive and significant effect on company value. Liquidity had a negative and significant effect on company value.